Morphological heterogeneity and population differentiation in the green chromid Etroplus suratensis (Pisces: Cichlidae) in Sri Lanka - K. B. Suneetha Gunawickrama (Ruhuna Journal of Science, 2007)
Morphological variation of the euryhaline cichlid fish Etroplus suratensis (Bloch) from six geographically apart estuarine localities along the southern and western coasts of Sri Lanka was studied. Significant heterogeneity in morphology of the cichlid were found with respect to nine morphometric characters (n=218). Fish of Nilwala estuary and Garanduwa lagoon were not significantly different in morphology, yet they show discernible differences from the other four samples (Kahanda lagoon, Chilaw lagoon, Walawe estuary and Koggala lagoon) with respect to the most of the studied characters. Concordant results were found by multivariate analysis of the sizecorrected morphological data as well. Three functions were significant in discriminating the populations of which the first two functions accounted for 95% of the covariance (CV1 85.4 % and CV2 9.7%). The function with the greatest discriminatory power (CV1) can clearly separate samples of Nilwala estuary (L5) and Garanduwa lagoon (L6) from the rest of the samples, while the magnitude of the discrimination between the latter samples is much smaller. Classification functions could correctly classify an average of 65.7% of the individuals into their respective a priori population units. No evidence was found for isolation-by-distance model. The results suggest that E. suratensis populations in some of the studied estuarine localities maintain significant morphological heterogeneity, and the morphological variation can be used to differentiate some of these populations.